2008
DOI: 10.1159/000162112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fat Embolism with Triolein Emulsion on Blood-Retinal Barrier

Abstract: Background: Triolein emulsion is under investigation for supplemental use to open the blood-brain barrier during chemotherapy. The effects of triolein emulsion on the blood-retinal barrier (BRB) were investigated. Methods: Fat emboli were induced in 20 cats by injecting triolein emulsion through the carotid artery. At 30 min, 4, 12 and 48 h after embolization, electroretinography (ERG) and fluorescein angiography (FA) were performed. The eyeballs were enucleated for transmission electron-microscopic study. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The results indicated that the diffuse disruption of BRB was caused by free fatty acid, which resulted from hydrolyzing neutral fat, and the interval represented time for releasing sufficient fatty acid. 3,8 However, the diffuse leakage in the late phase in the present study cannot be explained with either the mechanical injury or the fatty acid theory.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…The results indicated that the diffuse disruption of BRB was caused by free fatty acid, which resulted from hydrolyzing neutral fat, and the interval represented time for releasing sufficient fatty acid. 3,8 However, the diffuse leakage in the late phase in the present study cannot be explained with either the mechanical injury or the fatty acid theory.…”
Section: Discussionmentioning
confidence: 49%
“…Multifocal leakage in the early phase suggests that mechanical trauma by a fat droplet would cause the endothelium damage that was shown in a previous study. 8 The FA and electroretinogram study of the cats' eyes showed that the peak time of the BRB disruption was 4 hr after the infusion of triolein. The results indicated that the diffuse disruption of BRB was caused by free fatty acid, which resulted from hydrolyzing neutral fat, and the interval represented time for releasing sufficient fatty acid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various degrees of perfusion defects were demonstrated in the retina and choroid. The difference in degrees was due to the various sizes of triolein emulsion droplets 18 . Stop-and-go movements of intravascular lipid drops were observed in the retinal vessels, and the perfusion defects were resolved in most areas in the late phase.…”
Section: Resultsmentioning
confidence: 99%